Perceived Mentoring Practices in Developmental-Behavioral Pediatrics Fellowship Programs. Issue 4 (May 2017) - Diekroger, Elizabeth A.; Reyes, Charina; Myers, Katherine M.; Li, Hong; Kralovic, Shanna K.; Roizen, Nancy
ABSTRACT: Objective: Junior physicians describe mentoring relationships as integral to their career development and success. Current evidence suggests that mentoring is under-utilized despite interest from trainees. The purpose of this study is to describe the mentoring practices in developmental-behavioral pediatric (DBP) fellowship programs and identify mentoring needs of DBP fellows and recent graduates. Methods: DBP fellows and recent graduates less than 5 years out of training from US-based DBP fellowship programs were contacted to complete a survey on their mentoring experiences in fellowship and early career. Results: A total of 90 respondents completed the entire survey including 47 current DBP fellows and 43 recent graduates. Only 52% of respondents reported having a formal faculty mentor during their fellowship. Only 45% of recent graduates reported that they currently have a mentor, of those without a current mentor 83% said they would like to have a mentor. Adequate mentoring during fellowship was lowest for career development and research (34% and 27%). Satisfaction with mentoring was associated with having a formal mentor ( p < .001) and receiving mentoring in multiple areas ( p < .001). Qualitative responses suggested that effective mentoring addresses the mentee's career goals, provides insight into being a developmental-behavioral pediatrician, assists in navigating academics, and involves a personal relationship. Conclusion: Results suggest opportunities for improved mentoring in DBP fellowship programs, particularly in the areas of career development and research and that there is a significant need for mentorship among recent graduates. Findings from this study can inform program improvement in mentoring for DBP fellows and recent graduates. Abstract : This article has supplementary material on the web site: www.jdbp.org.